PEMANFAATAN TEKNOLOGI DIGITAL GOOGLE MAPS DAN MEDIA SOSIAL DALAM PENGEMBANGAN UMKM DESA BUKIT MAS - Isna Mawaddah; Hasfie Fauzan; Dwi Novita; T. Muhammad Farhan Abdillah; Syafruddin Syam (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the national economy, yet they often face challenges due to limited resources and traditional marketing strategies. This study aims to describe the development efforts for MSMEs in Bukit Mas Village, specifically focusing on Warung Ibu Sumiati, through the utilization of digital technology and the strengthening of visual identity. The methods employed in this community service program include field observation, needs identification, branding design (logos and banners), location registration on Google Maps via the Google Business Profile feature, as well as training and mentoring for the business owner. The results of the activity indicate that the implementation of a professional visual identity is able to enhance the business image and brand awareness among the community. Furthermore, the use of Google Maps and WhatsApp proved effective in increasing business visibility and accessibility, making it easier for new customers to find the location and place orders. Overall, this program confirms that simple, low-cost, and applicable digitalization strategies can serve as a primary foundation for MSMEs to enhance their competitiveness in the digital era.